Life and times of Dyal Singh Majithia - Madan Gopal (New Delhi, India : Uppal Pub. House, 1999)
Biography of Dyal Singh Majithia, 1848-1898, educationist, businessman, and founder of the Tribune, English daily newspaper.
Includes bibliographical references (p. 239-244).
Keywords: Majithia, Dyal Singh, -- 1848-1898; Educators -- India -- Punjab -- Biography; Businessmen -- India -- Punjab -- Biography; Philanthropists -- India -- Punjab -- Biography; Punjab (India) -- Biography